(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2025)
The integration of modern technologies into music education has transformed the way students learn and practice music, providing new opportunities to develop musical skills. The use of applications, interactive platforms, and software programs has enhanced the learning experience, offering a more personalized, engaging, and accessible approach to music education. This article explores the benefits and challenges of using technological tools in music education, focusing on how various digital platforms can improve musical skills, foster creativity, and provide students with more opportunities for practice and performance. The article also discusses how these technologies can complement traditional teaching methods and help bridge the gap between formal music education and informal, self-directed learning.